2022
DOI: 10.1002/app.53274
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CeO2 on UV aging of composite insulators prepared by template‐spraying method

Abstract: When the silicone rubber composite insulator is exposed outdoors for a long time, it will be affected by high-temperature ultraviolet environments. In order to ensure the operation of silicone rubber composite insulators, a superhydrophobic composite insulator with antiaging characteristics was prepared by mixing cerium dioxide (CeO 2 ) with silicone rubber and spraying CeO 2 on the surface of silicone rubber. This article studied the aging characteristics of the base and surface of silicone rubber composite i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In addition to the reinforcing filler silica, the filler commonly used in SIR composite insulators also has ATH for the purpose of improving the insulation performance and heat resistance of the insulator [ 9 , 10 ]. Among the fillers, the effect of ATH and silica fillers with different types, sizes and concentrations are extensively investigated in laboratory studies [ 11 , 12 , 13 , 14 ]. Samuel Ansorge et al [ 15 ] found that the SIR composite material with ATH had better performance than that without ATH.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the reinforcing filler silica, the filler commonly used in SIR composite insulators also has ATH for the purpose of improving the insulation performance and heat resistance of the insulator [ 9 , 10 ]. Among the fillers, the effect of ATH and silica fillers with different types, sizes and concentrations are extensively investigated in laboratory studies [ 11 , 12 , 13 , 14 ]. Samuel Ansorge et al [ 15 ] found that the SIR composite material with ATH had better performance than that without ATH.…”
Section: Introductionmentioning
confidence: 99%
“…However, the prolonged exposure of composite insulators to electric fields, ultraviolet light, acid rain, and fouling leads to their aging and deterioration of electrical and mechanical properties, which potentially jeopardizes the power supply reliability of the power grid [2]. Therefore, testing the performance of composite insulators, assessing the degree of insulator aging, determining whether replacements are necessary, troubleshooting the power grid, and improving the efficiency of equipment condition maintenance are critical to ensuring the safe operation of the power system [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Superhydrophobic coatings have attracted much attention due to their potential applications in solar-power devices, 9 metal corrosion, 10 and communication equipment. 11,12 The wettability of the object surface is determined by the surface chemical composition and the micro-geometry structure. 13,14 There is a scientific consensus that low surface energy materials combined with surface micro-nano structures can obtain superhydrophobic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, rigid nanoparticles are needed to provide a stable micro-nano structure skeleton. To meet the functional requirements of different fields, nanoparticles such as cerium dioxide (CeO 2 ), 11 titanium dioxide (TiO 2 ), 14,25 vanadium dioxide (VO 2 ), 26 and silicon dioxide (SiO 2 ) 7,8,45,46 are always applied to provide suitable surface micro-nanometer rough structures for the construction of superhydrophobic coatings. Among them, the production process of n-SiO 2 is highly mature, boasting not only low raw material costs but also the capability to meet extremely low particle size requirements ranging from 1 to 100 nm.…”
Section: Introductionmentioning
confidence: 99%